Energy storage phase change thermal insulation foam material and preparation method thereof

By mixing ester wax substances with biomass prepolymers and adding nanoparticles and foaming agents to the emulsion, energy storage phase change insulation foam materials are prepared, which solves the problems of low insulation efficiency of existing phase change materials and complex preparation methods, and achieves efficient heat insulation and environmentally friendly energy storage phase change insulation effects.

CN119875190AActive Publication Date: 2025-04-25HUAZHONG AGRI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510056314.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The insulation efficiency of existing phase change materials is limited, with poor stability and environmental adaptability, and complex preparation methods, making it difficult to meet the market's demand for high-efficiency insulation products.

Method used

Ester wax substances or molten ester substances are mixed with biomass prepolymers, nanoparticles and initiators are added, and water-in-oil Pickering emulsion is constructed and foaming agent is added. Finally, energy storage phase change insulation foam material is prepared by heating curing method.

Benefits of technology

It improves the latent heat and phase change temperature range of the material, enhances mechanical properties, reduces heat conduction, and improves heat insulation performance. It also has a simple process, high efficiency, low cost, and green and environmentally friendly material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875190A_ABST
    Figure CN119875190A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage materials, in particular to an energy storage phase change thermal insulation foam material and a preparation method thereof. The preparation method comprises the following steps: melting, heating and mixing a phase change material and an oil phase to obtain a first mixed oil phase; the phase change material is an ester wax substance or a molten ester substance; the oil phase is a biomass prepolymer; adding nanoparticles and an initiator into the first mixed oil phase to obtain a second mixed oil phase; adding the water phase into the second mixed oil phase, and mechanically stirring and emulsifying to obtain a water-in-oil Pickering emulsion; the preparation method comprises the following steps: adding a foaming agent into a water-in-oil Pickering emulsion to obtain a pre-foamed emulsion; and pouring the pre-foamed emulsion into a mold, heating and curing, and drying after curing to obtain the energy-storage phase-change thermal-insulation foam material. The preparation method has the advantages of being green, non-toxic, easy to operate, high in efficiency and low in cost. The prepared energy-storage phase-change thermal insulation foam material is low in heat conductivity coefficient, good in mechanical property and large in heat storage capacity, and can be used in various fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy storage materials, and in particular to an energy storage phase change thermal insulation foam material and a preparation method thereof. Background Art

[0002] In today's society, thermal insulation foams derived from petroleum are increasingly polluting the ecological environment. Porous foams, porous sponges, aerogels and other products produced with biomass as raw materials have become one of the hot spots in current material science research due to their advantages of being renewable, degradable and environmentally friendly. With the gradual improvement of people's living standards and the pursuit of health and convenience, the market demand for thermal insulation products is growing. Especially in the fields of food preservation, beverage insulation and medical transportation, the quality of thermal insulation directly affects the quality and safety of the product. However, traditional thermal insulation materials usually rely on thermal insulation materials to reduce heat transfer. This method can maintain temperature in a short period of time, but in long-term use, the thermal insulation effect is often difficult to meet actual needs.

[0003] Phase change materials (PCM) are widely used in the field of temperature control because they can absorb or release a large amount of heat during the phase change process. These materials adjust the ambient temperature through phase transitions (such as solid-liquid, liquid-gas, etc.) when the temperature changes, and can provide stable temperature output when the ambient temperature changes. However, most of the phase change material application products on the market still have some disadvantages, such as limited insulation efficiency, volume and weight issues, stability of phase change materials, poor environmental adaptability, etc.

[0004] The thermal insulation material prepared with energy storage phase change material is made of animal and plant extracts or derivatives, such as soybean oil derivatives (epoxidized soybean oil acrylate, lignin-based acrylate, etc.), carbohydrates or their derivatives (ethyl cellulose, chitin), phase change materials (palm wax, rice bran wax, beeswax, fatty acid esters, etc.) as raw materials, and finally forms a foam material with good energy storage effect through the steps of mixing into emulsion, reaction curing, heating and drying. For example, the patent with application number CN201910120219.8 provides a filter residue material with phase change energy storage properties obtained by preparing a pre-emulsion and then undergoing a polymerization reaction. For example, the patent with application number CN202310118691.4 discloses the preparation of phase change energy storage materials by using raw materials such as paraffin, sodium dodecyl sulfate, and dimethyl silicone oil. Although the above methods have certain effects, their preparation methods are complicated and cumbersome, and mostly involve the use of chemical organic reagents, which does not conform to the concept of green manufacturing. Therefore, it is particularly important to develop a new type of energy storage phase change thermal insulation foam material that can utilize the heat storage and release characteristics of phase change materials to achieve long-term temperature maintenance and meet the market's urgent demand for high-efficiency thermal insulation products. Summary of the invention

[0005] In order to solve or partially solve the problems existing in the related art, the present invention provides an energy storage phase change thermal insulation foam material and a preparation method thereof.

[0006] The present invention provides a method for preparing an energy storage phase change thermal insulation foam material, which comprises:

[0007] Step a), melting and heating a phase change material and an oil phase to obtain a first mixed oil phase; the phase change material is an ester wax substance or a fusible ester substance; the oil phase is a biomass prepolymer;

[0008] Step b), adding nanoparticles and an initiator to the first mixed oil phase to obtain a second mixed oil phase;

[0009] Step c), adding the water phase to the second mixed oil phase, and mechanically stirring and emulsifying to obtain a water-in-oil Pickering emulsion;

[0010] Step d), adding a foaming agent to the water-in-oil Pickering emulsion to obtain a pre-foamed emulsion;

[0011] Step e), pouring the pre-foamed emulsion into a mold, heating and curing it, and drying it after curing to obtain an energy storage phase change thermal insulation foam material.

[0012] Furthermore, the ester wax substance is one or more of beeswax, insect wax, palm wax, and rice bran wax; the fusible ester substance is one or more of stearic acid ester, hydrogenated castor oil, and fatty acid ester.

[0013] Furthermore, the mixing ratio of the phase change material to the oil phase is 1-15:100 by weight.

[0014] Furthermore, the nanoparticles are organic nanoparticles and / or inorganic nanoparticles; the organic nanoparticles are ethyl cellulose nanoparticles, chitin nanoparticles, or phase change nanoparticles, and the phase change nanoparticles are nanoparticles made of phase change materials with a melting temperature higher than 80°C; the inorganic nanoparticles are silicon dioxide particles, calcium carbonate particles or zinc oxide particles; the amount of the organic nanoparticles added to the first mixed oil phase is 2-12wt%; the amount of the inorganic nanoparticles added to the first mixed oil phase is 0.3-1.8wt%.

[0015] Furthermore, the initiator is benzoyl peroxide, lauroyl peroxide or tert-butyl perbenzoate; the added amount of the initiator is 2-3wt% of the first mixed oil phase.

[0016] Furthermore, the foaming agent is bicarbonate, and the added amount of the foaming agent is 0.1-1.5wt% of the water-in-oil Pickering emulsion.

[0017] Furthermore, in the step c), the mixing ratio of the second mixed oil phase to the water phase is 6-9:1-4.

[0018] Furthermore, in the step e), the temperature of heating and curing is 70-100° C., and the time is 1.5-6 hours; the temperature of drying is 50-60° C., and the time is 6-8 hours.

[0019] Furthermore, in the step e), the mold material is polytetrafluoroethylene, high borosilicate or stainless steel.

[0020] The present invention also provides an energy storage phase change thermal insulation foam material, which is prepared according to any one of the methods described above.

[0021] The energy storage phase change thermal insulation foam material and the preparation method thereof provided by the present invention may have the following beneficial effects:

[0022] 1) This method melts and mixes the phase change material and the oil phase as a mixed oil phase. The phase change material uses ester wax substances or fusible ester substances, and the oil phase uses biomass prepolymer. On the one hand, the above-mentioned phase change material has better compatibility with the oil phase and can be mixed more evenly. Such a combination can make it better combined at the molecular level, avoid separation or performance degradation of the material during the phase change process, and increase the phase change latent heat and phase change temperature range of the material; on the other hand, ester wax substances (such as palm wax) in the solid state have high rigidity and toughness. When added to the reaction system, it can not only strengthen the cross-linking process of the material, but also improve the mechanical properties of the material. It improves the shortcomings of poor mechanical strength and wear resistance of the product due to low cross-linking degree or insufficient raw material properties when only a single prepolymer is used, and further improves its impact resistance and durability in application scenarios such as transportation and storage.

[0023] 2) The raw materials involved in the preparation method, except for a small amount of inorganic substances, can all be derived from biomass materials, so the method has the advantages of being green, non-toxic, widely available, and easy to obtain. Among them, biomass materials also have the social and economic benefits of waste utilization, and have the potential to be biodegradable, thereby realizing the greening and safety of foam materials from the source.

[0024] 3) This method adds a foaming agent to the emulsion to further increase the number of emulsion pores. The formed pores can capture and maintain air stability, forming an air layer, thereby greatly limiting the flow of heat, thereby reducing the structural density caused by the introduction of phase change materials, reducing the thermal conductivity of the foam material, and improving the thermal insulation performance of the foam material. Furthermore, the foaming agent can be ammonium bicarbonate, sodium bicarbonate, etc. These reagents are widely available, cheap and easy to obtain, and the decomposition products produced when heated, such as ammonia, carbon dioxide, water, etc., are not harmful factors in the environment, which is beneficial to environmental protection.

[0025] 4) This method constructs a W / O type Pickering emulsion, uses the Pickering emulsion as a template, and solidifies the template (oil phase) by heating to produce energy storage phase change thermal insulation foam materials. This process only involves common basic equipment such as mechanical agitators, water baths, ovens, etc., avoiding dependence on special equipment (such as high-pressure reaction devices, high-speed shear equipment, freeze-drying equipment), and special reaction conditions (such as high temperature and high pressure, low temperature and negative pressure). The foam molding process is relatively simple in design. Through one-time addition and molding, and one-time heating molding, it avoids multiple compounding and complex chemical treatments in traditional foam molding processes such as gel sol-freeze drying methods, improves production efficiency and molding yield, and reduces molding costs. Therefore, this preparation method has the advantages of easy operation, high efficiency, and low cost.

[0026] 5) The energy storage phase change thermal insulation foam material prepared by this method has a large number of pores with small pore diameters, low thermal conductivity, good mechanical properties, and large heat storage capacity, and can be used in a variety of fields.

[0027] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0029] Figure 1 It is the DSC graph of the energy storage phase change thermal insulation foam material prepared in Examples 1-6 of the present invention;

[0030] Figure 2 This is a diagram showing the appearance of the energy storage phase change thermal insulation foam material prepared in Examples 1-6 of the present invention;

[0031] Figure 3 This is a test diagram of the mechanical properties of the energy storage phase change thermal insulation foam material prepared in Examples 1-6 of the present invention;

[0032] Figure 4 This is a diagram showing the appearance of the energy storage phase change thermal insulation foam material obtained in Examples 13 and 14 of the present invention;

[0033] Figure 5 It is the appearance diagram of the energy storage phase change thermal insulation foam material prepared in Examples 3 and 13 of the present invention;

[0034] Figure 6 The foam material prepared in Example 3 of the present invention ( Figure 6a) and the foam material prepared in Comparative Example 3 ( Figure 6 b) SEM image;

[0035] Figure 7 Embodiment 3 of the present invention ( Figure 7 a), Comparative Example 1 ( Figure 7 c) and Comparative Example 2 ( Figure 7 b) Appearance of the prepared foam material. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "the" and "the" used in the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0038] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0039] The embodiment of the present invention provides a method for preparing an energy storage phase change thermal insulation foam material, which comprises the following steps:

[0040] Step a), melting and heating a phase change material and an oil phase to obtain a first mixed oil phase; the phase change material is an ester wax substance or a fusible ester substance; the oil phase is a biomass prepolymer;

[0041] Step b), adding nanoparticles and an initiator to the first mixed oil phase to obtain a second mixed oil phase;

[0042] Step c), adding the water phase to the second mixed oil phase, and mechanically stirring and emulsifying to obtain a water-in-oil Pickering emulsion;

[0043] Step d), adding a foaming agent to the water-in-oil Pickering emulsion to obtain a pre-foamed emulsion;

[0044] Step e), adding the pre-foamed emulsion into a mold, heating and curing it, and drying it after curing to obtain an energy storage phase change thermal insulation foam material.

[0045] In the above preparation method, step a) is to melt and mix the phase change material with the oil phase, so that the phase change material is evenly dispersed in the oil phase, and the bonding degree is improved by using the principle of like dissolves like, thereby obtaining the first mixed oil phase. This step can be specifically:

[0046] heating and melting the phase change material;

[0047] Add the oil phase into the molten phase change material and mix thoroughly;

[0048] The mixture was allowed to stand and cool to obtain the first mixed oil phase.

[0049] In this embodiment, the phase change material is an ester wax material or a fusible ester material, which can be specifically one or more of beeswax, insect wax, palm wax, and rice bran wax; the oil phase is a biomass prepolymer, which can be specifically one or more of stearate, hydrogenated castor oil, and fatty acid ester. The above-mentioned phase change material has better compatibility with the oil phase and can be mixed more evenly. Such a combination can make it better combined at the molecular level, avoid separation or performance degradation of the material during the phase change process, and increase the phase change latent heat and phase change temperature range of the material. In addition, the raw materials of the above-mentioned phase change material come from natural raw materials, and the oil phase material is a soybean oil derivative, carbohydrate or its derivative from natural sources. This avoids the use of chemical raw materials that are harmful to the environment, such as petroleum-based derivatives, and improves the environmental friendliness of the product. Further, the mixing ratio of the phase change material to the oil phase is 1-15:100 by weight, while ensuring that the material has good phase change properties while maintaining sufficient strength and toughness. The mixing ratio of the phase change material to the oil phase is more preferably 5-10:100 by weight.

[0050] The above step b) is a step of mixing nanoparticles and initiators into the first mixed oil phase. The nanoparticles act as Pickering emulsifiers to stabilize the W / O type emulsion, prevent oil-water separation, and ensure the stability of the foam structure. The thermal initiator is used to initiate the curing reaction of the oil phase, so that the oil phase forms a three-dimensional network structure, thereby improving the strength and toughness of the material. The nanoparticles are organic nanoparticles and / or inorganic nanoparticles; the organic nanoparticles are ethyl cellulose nanoparticles, chitin nanoparticles, or phase change nanoparticles, and the phase change nanoparticles are nanoparticles made of phase change materials with a melting temperature higher than 80°C; the inorganic nanoparticles are silicon dioxide particles, calcium carbonate particles, or zinc oxide particles. The raw materials of the above nanoparticles are all from natural raw materials, thereby further improving the environmental protection of the product and its preparation process. The addition amount of the organic nanoparticles in the first mixed oil phase is preferably 2-12wt%, more preferably 2-4wt%, and most preferably 4wt%; the addition amount of the inorganic nanoparticles in the first mixed oil phase is preferably 0.3-1.8wt%, more preferably 0.6-1.2wt%. The particle size of the above-mentioned nanoparticles is preferably 150-1200nm. Among the above-mentioned organic nanoparticles, if phase change nanoparticles are used, it will be more helpful to improve the heat storage performance of the foam product. At that time, the inventors found through research that if the melting temperature of the phase change material of the phase change nanoparticles is lower than 80°C, it will cause the solidified product to be difficult to form, or the mechanical properties of the formed product will be too poor. Therefore, the phase change nanoparticles of the present application are nanoparticles made of phase change materials with a melting temperature higher than 80°C. The phase change nanoparticles can be prepared according to the following method: after mixing the phase change material with water, heating until the phase change material melts; then adding an emulsifier, such as Tween 20, and magnetically stirring to obtain a phase change material particle pre-dispersion; then performing ultrasonic treatment to obtain a phase change material nanoparticle water dispersion, which is concentrated for use. The mixing mass ratio of the phase change material to water is preferably 1: (55-65), and the most preferred is 1:50. The speed of magnetic stirring is preferably 700-900r / min, the time is preferably 20-40min, and most preferably, the speed of magnetic stirring is 800r / min, and the time is 30min. The amplitude of ultrasonic treatment is preferably 60%-80%, ultrasonic 4-6s, intermittent 4-6s, and most preferably, the amplitude is 70%, ultrasonic 5s, and intermittent 5s. The time of ultrasonic treatment is preferably 4-6min, and most preferably 5min.

[0051] The initiator used in this step is preferably benzoyl peroxide, lauroyl peroxide or tert-butyl perbenzoate; the amount of the initiator added is 2-3wt% of the first mixed oil phase, and benzoyl peroxide is most preferably used, and the amount added is 3wt% of the first mixed oil phase; the cross-linking agent in the above proportion can effectively control the speed and degree of the curing reaction, avoid excessive cross-linking or incomplete cross-linking of the material, thereby ensuring the performance of the product.

[0052] The above step c) is to mix and emulsify the water phase and the second mixed oil phase to form a stable water-in-oil Pickering emulsion, which provides a template for subsequent foaming and curing. In this step, the mixing ratio of the second mixed oil phase and the water phase is preferably 6-9:1-4, and most preferably 6:4. The emulsification method in this step is mechanical stirring emulsification, the stirring rate is preferably 100-300r / min, and the stirring time is preferably 15-30min to ensure the stability of the emulsion and the uniformity of the foam structure.

[0053] In the case where the mixing ratio of the phase change material to the oil phase in the first mixed oil phase is greater than 5:100, conventional mixing will result in excessive viscosity of the mixed oil phase and failure to form an emulsion due to crystallization behavior. For this reason, step b) and step c) need to be heated for compensation, i.e., performed under heating conditions. The heating temperature is preferably 40-50°C, more preferably 45°C, as follows:

[0054] Step b) softening the second mixed oil phase under heating in a water bath; then sequentially adding solid nanoparticles and an initiator to the second mixed oil phase, stirring, and mixing uniformly to obtain a second mixed oil phase;

[0055] Step c), adding the aqueous phase to the second mixed oil phase under heating in a water bath, and mechanically stirring and emulsifying to obtain a water-in-oil Pickering emulsion;

[0056] The above step d) is a step of adding a foaming agent to the water-in-oil Pickering emulsion. The inventors of the present application have found through research that the thermal insulation performance of the product obtained by directly pouring and curing the water-in-oil Pickering emulsion is still not ideal. Further analysis shows that it may be related to the addition of phase change materials, which causes the internal structure of the product to be too dense. In order to further improve the thermal insulation performance, the inventors consider increasing the number of pores in the emulsion. These pores can capture and maintain air stability to form an air layer, thereby greatly limiting the flow of heat. Therefore, the method for preparing an energy storage phase change thermal insulation foam material provided by the present invention adds a foaming agent to the Pickering emulsion. For the selection of the foaming agent, the present application preferably uses bicarbonate, for example, ammonium bicarbonate, sodium bicarbonate or calcium bicarbonate; the amount of bicarbonate added is 0.1-1.5wt% of the water-in-oil Pickering emulsion, which can effectively control the porosity and thermal insulation performance of the foam structure. The foaming agent has a thermal demand that is synchronized with the curing reaction, that is, it can be thermally decomposed at the temperature of heating and curing to produce gas to promote the formation of holes. The most preferred foaming agent is ammonium bicarbonate. During the heating and curing process of ammonium bicarbonate, the carbon dioxide and ammonia generated promote pore formation, and the decomposition products will not have any impact on the environment, which helps to improve environmental protection performance.

[0057] The above step e) is a step of pouring, heating and curing and drying. The heating process can solidify the oil phase to form a foam structure. After the curing reaction, there is still a large amount of water vapor (water phase) in the reaction mold, and the thermal insulation material is in a highly humid state. It is dried and matured to remove moisture, and finally an energy storage phase change thermal insulation foam material is obtained. In this step, the temperature of heating and curing is preferably 70-100°C, and the time can be 1.5-6h, and the drying temperature is preferably 50-60°C, and the time is 8-10h, so as to ensure the molding quality and mechanical properties of the material. More preferably, the temperature of heating and curing is 80°C, the time is 3h, and the drying temperature is 55°C, and the time is 8h.

[0058] The mold material used in this step is preferably polytetrafluoroethylene, high borosilicate or stainless steel. Using different molds can produce different materials with oil film wrapping. In the polytetrafluoroethylene mold, due to its lower surface energy, the droplet will form a large angle of contact angle on the mold surface, showing significant repellency, which causes the water phase to be difficult to be wetted or expanded by its surface, and cannot form a uniform water layer on the mold surface, so no oil film is produced. The surface energy of the high borosilicate mold makes it easy for the water phase to expand on the mold surface, so that the oil phase in the emulsion is wrapped by the water phase and pushed to the mold surface. During the curing process, the oil phase gradually gathers and solidifies on the mold surface to form an oil film.

[0059] During the pouring process, in order to provide space for the volume expansion of the emulsion after foaming, the pouring volume of the pre-foamed emulsion is preferably 30-70% of the mold volume fraction. The mold preferably has a pressure relief mechanism, which is used to ensure that the pressure inside the mold is slightly higher than the external pressure, thereby restricting the formation and growth of bubbles in the emulsion.

[0060] Another embodiment of the present invention provides an energy storage phase change thermal insulation foam material, which is prepared according to the method described in the above embodiment. The energy storage phase change thermal insulation foam material has a large number of pores with small pore diameters, low thermal conductivity, good mechanical properties, and large heat storage capacity, and can be used in a variety of fields.

[0061] It can be seen from the above content that the energy storage phase change thermal insulation foam material and the preparation method thereof provided in the embodiments of the present invention have the following advantages:

[0062] 1) This method melts and mixes the phase change material and the oil phase as a mixed oil phase. The phase change material uses ester wax substances or fusible ester substances, and the oil phase uses biomass prepolymers. On the one hand, the above-mentioned phase change material has better compatibility with the oil phase and can be mixed more evenly. Such a combination can make them better combined at the molecular level, avoid separation or performance degradation of the material during the phase change process, and increase the phase change latent heat and phase change temperature range of the material. On the other hand, ester wax substances (such as palm wax) have higher hardness characteristics. Adding them to the reaction system can not only strengthen the cross-linking process of the material, but also improve the mechanical properties of the material. It improves the shortcomings of poor mechanical strength and wear resistance of the product caused by low degree of cross-linking or insufficient raw material properties when only a single prepolymer is used, and further improves its impact resistance and durability in application scenarios such as transportation and storage.

[0063] 2) The raw materials involved in the preparation method, except for a small amount of inorganic substances, can all be derived from biomass materials, so the method has the advantages of being green, non-toxic, widely available, and easy to obtain. Among them, biomass prepolymer materials also have the social and economic benefits of waste utilization, and have the potential to be biodegradable, thereby realizing the greening and safety of foam materials from the source.

[0064] 3) This method adds a foaming agent to the emulsion to increase the number of pores in the emulsion. The formed pores can capture and maintain air stability to form an air layer, thereby greatly limiting the flow of heat, thereby reducing the microstructure density caused by the introduction of the phase change material, reducing the thermal conductivity of the foam material, and improving the thermal insulation performance of the foam material. Furthermore, the foaming agent can be ammonium bicarbonate, sodium bicarbonate, etc. These reagents are widely available, cheap and easy to obtain, and the decomposition products generated when heated, such as ammonia, carbon dioxide, water, etc., are not harmful factors in the environment, which is beneficial to environmental protection.

[0065] 4) This method constructs a W / O type Pickering emulsion, uses the Pickering emulsion as a template, and solidifies the template (oil phase) by heating to produce energy storage phase change thermal insulation foam materials. This process only involves common basic equipment such as mechanical stirrers, water baths, ovens, etc., avoiding dependence on special equipment (such as high-pressure reaction devices, high-speed shear equipment, freeze dryers), and special reaction conditions (such as high temperature and high pressure, low temperature and negative pressure). The foam molding process is relatively simple in design. Through one-time addition and molding, and one-time heating and molding, it avoids multiple compounding and complex chemical treatments in traditional foam molding processes such as gel sol-freeze drying methods, improves production efficiency and molding yield, and reduces molding costs. Therefore, this preparation method has the advantages of easy operation, high efficiency, and low cost.

[0066] 5) The energy storage phase change thermal insulation foam material prepared by this method has a large number of pores with small pore diameters, low thermal conductivity, good mechanical properties, and large heat storage capacity, and can be used in a variety of fields.

[0067] The technical solution of the present invention is further described below in conjunction with specific embodiments:

[0068] The sources of the raw materials used in the following examples are as follows:

[0069] Palm wax: purchased from Shanghai Jiujie Industrial Co., Ltd. (origin: Brazil);

[0070] Beeswax: purchased from Henan Xuchang Yihengjian Bee Industry Co., Ltd.;

[0071] Castor wax: purchased from Global (Hong Kong) Agency Co., Ltd. (origin: Thailand);

[0072] Rice bran wax: purchased from Chongqing Hecai Chemical Technology Co., Ltd.;

[0073] Fatty acid esters: purchased from Guangzhou Huayu Biotechnology Co., Ltd.; Epoxidized soybean oil acrylate: purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., biomass content>90%, epoxidation value 6.28;

[0074] Ethyl cellulose nanoparticles: purchased from Shanghai Sigma Co., Ltd.

[0075] Silica nanoparticles: purchased from Shanghai Sigma Co., Ltd.

[0076] Example 1

[0077] (1) Weigh 0.171 g of palm wax and 17.0 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0078] (2) adding 4 wt % of ethyl cellulose having an average particle size of 150 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and mixing them evenly to obtain a second mixed oil phase;

[0079] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0080] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0081] (5) The physical properties of the obtained energy storage phase change thermal insulation foam material are analyzed as follows: the apparent density is 0.198 g / cm 3 , thermal conductivity is 0.067W / m·K, thermal diffusivity is 0.21mm 2 / s, compression strength 0.35MPa, heat storage capacity 1.18J / g.

[0082] The method of physical property analysis is as follows, the same as in the following examples:

[0083] ①Apparent density:

[0084] The sample is processed into a cylinder with a specification of Φ480×20mm. The sample mass is weighed using an analytical balance (with an accuracy of 0.001g). The apparent density of the sample is obtained by dividing the mass by the volume. It can be expressed as:

[0085]

[0086] Where ρ represents the apparent density of the sample, g / cm 3 ; m represents the sample mass, g; v represents the sample volume, cm 3 .

[0087] ②Performance test

[0088] The transient plane source method is used to test the room-temperature thermal conductivity of the sample. The specific test process is as follows: first, the assembled sample and the probe are placed in the furnace, and then the furnace is sealed and evacuated until the pressure in the furnace drops to 10Pa and maintained for 1 hour to fully desorb the gas adsorbed by the sample. Finally, air is slowly introduced into the furnace, and after reaching the set pressure and stabilizing for 2 hours, the thermal conductivity at the specified pressure is tested.

[0089] ③ Mechanical strength

[0090] The compression performance of porous materials was tested according to GB / T8813-2008 "Determination of compression performance of rigid foam plastics". The compression strength of the samples was tested using a WDW model 100 electronic universal testing machine. The specifications of the porous materials are a compression area of ​​314mm 2 A 48mm high cylinder was used to perform mechanical compression tests on porous materials using a 5000N force sensor. The experiment was conducted at a constant strain rate of 5mm / min until the sample collapsed. Each porous material was measured 3 times and averaged. Finally, the stress-strain curve of the material was obtained and the maximum compressive strength was calculated. The calculation formula is as follows:

[0091]

[0092] Among them, σ max Indicates the maximum compressive strength, Pa; Fmax Indicates the maximum force that the sample bears during compression, N; A indicates the cross-sectional area of ​​the sample, m 2 .

[0093] ④ Enthalpy change measurement

[0094] Use differential scanning calorimetry (DSC) to measure the enthalpy change process of the material during the phase change temperature change process and calculate the maximum absorbed or released heat energy. Accurately weigh 5-15 mg of the dried sample, place the sample in an appropriate DSC crucible, set the temperature range of the appropriate phase change material, and test at a heating rate of 5°C / min. The calculation formula is as follows:

[0095]

[0096] Where ΔH represents the enthalpy change of the sample within the temperature range, J / g; represents the heat flux density of the DSC curve, mW / mg; T1 and T2 represent the temperature range.

[0097] (6) The apparent density of the obtained energy storage phase change thermal insulation foam material is 0.192 g / cm 3 , thermal conductivity is 0.065W / m·K, thermal diffusivity is 0.19mm 2 / s, compression strength 0.213MPa, heat storage capacity 0.046J / g.

[0098] Example 2

[0099] (1) Weigh 0.43 g of palm wax and 16.74 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0100] (2) adding 4 wt % of ethyl cellulose with a particle size of 500 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and mixing them evenly to obtain a second mixed oil phase;

[0101] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0102] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0103] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.198 g / cm 3, thermal conductivity is 0.067W / m·K, thermal diffusivity is 0.21mm 2 / s, compression strength 0.244MPa, heat storage capacity 1.18J / g.

[0104] Example 3

[0105] (1) Weigh 0.86 g of palm wax and 16.31 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0106] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0107] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0108] (4) The pre-foamed emulsion is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80°C for 3 hours, and then dried at a constant temperature of 55°C for 8 hours after demolding to obtain an energy storage phase change thermal insulation foam material. The molds used in this embodiment and the following embodiments are all equipped with a pressure relief mechanism. When the pressure difference between the inside and outside of the mold is less than a preset value, such as 0.1-0.2MPa, the pressure relief mechanism is in a closed state; when the pressure difference between the inside and outside of the mold is greater than the preset value, the pressure relief mechanism is opened to reduce the pressure difference between the inside and outside of the mold until the pressure difference is reduced to the preset value. The specific implementation method of this embodiment is as follows: a capillary hole is opened at the top of the mold, and the adhesive strip covers the top of the capillary hole; when the pressure difference between the inside and outside of the mold is less than a preset value, such as 0.1-0.2MPa, the adhesive strip completely covers the capillary hole, and the mold is in a completely sealed state at this time; when the emulsion is heated in the mold, the foaming agent is thermally decomposed to produce bubble nuclei in the emulsion, and as the bubble nuclei grow, the volume of the emulsion increases, and the pressure in the mold cavity gradually increases. When the pressure difference between the inside and outside of the mold is greater than the preset value, the edge of the adhesive strip is lifted up by the action of air pressure, forming an air release path with the mold surface, and the mold is in a slow pressure relief state at this time; until the pressure difference between the inside and outside of the mold is lower than the preset value, the edge of the adhesive strip falls back to the state of mold bonding.

[0109] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.199 g / cm 3 , thermal conductivity is 0.068W / m·k, thermal diffusivity is 0.24mm 2 / s, compression strength 0.30MPa, heat storage capacity 1.627J / g.

[0110] Example 4

[0111] (1) Weigh 1.29 g of palm wax and 15.88 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0112] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0113] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0114] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0115] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.208 g / cm 3 , thermal conductivity is 0.072W / m·K, thermal diffusivity is 0.25mm 2 / s, compression strength 0.347MPa, heat storage capacity 1.897J / g.

[0116] Example 5

[0117] (1) Weigh 1.71 g of palm wax and 15.46 g of epoxy soybean oil acrylate, mix them, heat to melt at 90° C., and stir them evenly to obtain a first mixed oil phase;

[0118] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0119] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0120] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0121] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.213 g / cm 3 , thermal conductivity is 0.074W / m·K, thermal diffusivity is 0.32mm 2 / s, compression strength 0.364MPa, heat storage capacity 2.54J / g.

[0122] Example 6 (Blank Control Example without Phase Change Material)

[0123] (1) Weigh 17.17 g of epoxy soybean oil acrylate, add 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to obtain a mixed oil phase.

[0124] (2) Add the water phase (distilled water) to the mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stir at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion.

[0125] (3) adding 1 wt% ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0126] (4) The pre-foamed latex was poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain a biomass foam material.

[0127] (5) The physical properties of the prepared foam material were analyzed, and the apparent density was 0.196 g / cm 3 , thermal conductivity is 0.062W / m·K, thermal diffusivity is 0.30mm 2 / s, compression strength 0.135MPa, heat storage capacity 0.

[0128] Example 7

[0129] (1) Weigh 0.86 g of beeswax and 16.31 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0130] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0131] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0132] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 4 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0133] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.198 g / cm 3 , thermal conductivity is 0.068W / m·K, thermal diffusivity is 0.26mm 2 / s, compression strength 0.230MPa, heat storage capacity 1.437J / g.

[0134] Example 8

[0135] (1) Weigh 0.86 g of rice bran wax and 16.31 g of epoxidized soybean oil acrylate, mix them, heat to melt at 90° C., and stir them evenly to obtain a first mixed oil phase;

[0136] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0137] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0138] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0139] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.201 g / cm 3 , thermal conductivity is 0.071W / m·K, thermal diffusivity is 0.33mm 2 / s, compression strength 0.281MPa, heat storage capacity 1.624J / g.

[0140] Example 9

[0141] (1) Weigh 0.86 g of stearic acid ester and 16.31 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0142] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0143] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0144] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0145] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.20 g / cm 3 , thermal conductivity is 0.069W / m·K, thermal diffusivity is 0.36mm 2 / s, compression strength 0.281MPa, heat storage capacity 1.624J / g.

[0146] Example 10

[0147] (1) Weighing 0.86 g of palm wax and 16.31 g of lignin-based acrylate, mixing, heating to 90° C. to melt, and stirring evenly to obtain a first mixed oil phase;

[0148] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm, 0.6 wt % of silicon dioxide with a particle size of 200 nm, and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0149] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify and obtain a W / O type Pickering emulsion; adding 1 wt % ammonium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0150] (4) The pre-foamed latex is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0151] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.203 g / cm 3 , thermal conductivity is 0.068W / m·K, thermal diffusivity is 0.24mm 2 / s, compression strength 0.293MPa, heat storage capacity 1.627J / g.

[0152] Embodiment 11

[0153] (1) Weigh 0.86 g of palm wax and 16.31 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0154] (2) adding 2 wt % of ethyl cellulose with a particle size of 850 nm, 0.6 wt % of silicon dioxide with a particle size of 250 nm, and 2 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a 45° C. water bath. After the mixed oil phase softens, stirring and mixing the mixture uniformly obtains a second mixed oil phase;

[0155] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify to obtain a W / O type Pickering emulsion; adding 1 wt % sodium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0156] (4) The pre-foamed emulsion is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 90° C. for 2 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0157] (5) The physical properties of the prepared energy storage phase change thermal insulation foam material were analyzed: the apparent density was 0.198 g / cm3, the thermal conductivity was 0.070 W / m·K, the thermal diffusivity was 0.27 mm2 / s, the compressive strength was 0.294 MPa, and the heat storage capacity was 1.627 J / g.

[0158] Example 12

[0159] (1) Weigh 0.86 g of palm wax and 16.31 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0160] (2) adding 8 wt % of ethyl cellulose with a particle size of 850 nm, 1.2 wt % of silicon dioxide with a particle size of 300 nm, and 2 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a 45° C. water bath. After the mixed oil phase softens, stirring and mixing the mixture uniformly obtains a second mixed oil phase.

[0161] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify to obtain a W / O type Pickering emulsion; adding 1 wt % sodium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0162] (4) The pre-foamed emulsion is poured into a polytetrafluoroethylene cylindrical mold, heated and cured at 90° C. for 2 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0163] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.221 g / cm 3 , thermal conductivity is 0.070W / m·K, thermal diffusivity is 0.25mm 2 / s, compression strength 0.301MPa, heat storage capacity 1.627J / g.

[0164] Example 13

[0165] (1) Weigh 0.86 g of palm wax and 16.31 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0166] (2) adding 4 wt % of ethyl cellulose with a particle size of 850 nm and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a water bath at 45° C. After the mixed oil phase softens, stirring and mixing the mixture uniformly to obtain a second mixed oil phase;

[0167] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify to obtain a W / O type Pickering emulsion; adding 1 wt % sodium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0168] (4) The pre-foamed latex is poured into a borosilicate cylindrical mold, heated and cured at 80° C. for 3 h, and then dried at 55° C. for 8 h after demolding to obtain an energy storage phase change thermal insulation foam material.

[0169] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.202 g / cm 3 , thermal conductivity is 0.069W / m·K, thermal diffusivity is 0.26mm 2 / s, compression strength 0.303MPa, heat storage capacity 1.627J / g.

[0170] Embodiment 14

[0171] (1) Weigh 0.86 g of palm wax and 16.31 g of epoxy soybean oil acrylate, mix them, heat to 90° C. to melt, and stir them evenly to obtain a first mixed oil phase;

[0172] (2) adding 2 wt % of palm wax with a particle size of 600 nm, 3 wt % of benzoyl peroxide, and 3 wt % of benzoyl peroxide to the first mixed oil phase, and heating the mixture in a 45° C. water bath. After the mixed oil phase softens, stirring and mixing the mixture uniformly obtains a second mixed oil phase;

[0173] The preparation method of palm wax nanoparticles is as follows: add palm wax to distilled water with a wax-water ratio of 1:50, heat in a water bath until the palm wax melts, then add Tween 20, and stir magnetically at 800r / min for 30min; obtain a lipid particle predispersion; then treat with ultrasound (amplitude 70%, ultrasound 5s, interval 5s) for 5min to obtain a palm wax nanoparticle aqueous dispersion, which is concentrated for later use.

[0174] (3) adding the water phase (distilled water) to the second mixed oil phase with an oil-water mass ratio of 6:4, and mechanically stirring at 200 r / min for 30 min to emulsify to obtain a W / O type Pickering emulsion; adding 1 wt % sodium bicarbonate to the emulsion, continuing to stir and mix evenly to obtain a pre-foamed emulsion;

[0175] (4) The pre-foamed latex was poured into a high borosilicate square mold, heated and cured at 80°C for 3 hours, and then dried at 55°C for 8 hours after demolding to obtain an energy storage phase change thermal insulation foam material.

[0176] (5) Physical property analysis of the prepared energy storage phase change thermal insulation foam material: the apparent density is 0.203 g / cm 3 , thermal conductivity is 0.074W / m·K, thermal diffusivity is 0.34mm 2 / s, compression strength 0.185MPa, heat storage capacity 2.236J / g.

[0177] Comparative Example 1

[0178] Refer to step (1) to step (5) of Example 14, except that the palm wax in step (3) is replaced by beeswax (melting point <80°C). As a result, the expected energy storage phase change material cannot be formed. Since the catalytic reaction of the foam needs to be carried out at >80°C, when it is in this ambient temperature, the phase change material with a melting point of <80°C will melt and leak out before the oil phase solidifies, causing the emulsion structure to become unstable and destroyed, and the water phase droplets therein merge and become larger on a large scale, causing the prepared foam pores to expand or collapse.

[0179] Comparative Example 2

[0180] The pre-foamed emulsion was prepared according to steps (1) to (3) of Example 3, and then the pre-foamed emulsion was poured into a polytetrafluoroethylene mold, which was completely sealed (the pressure relief mechanism was closed), and heated at 80°C for curing. As a result, the expected energy storage phase change material could not be formed. This is because in a completely sealed mold, the gas generated by the foaming agent cannot escape, resulting in excessive pressure inside the mold cavity, thereby inhibiting the growth or expansion of the bubble nucleus in the emulsion and the stability of the bubble nucleus.

[0181] Comparative Example 3

[0182] The emulsion was prepared according to steps (1) to (3) of Example 10, except that no foaming agent was added in step (3). The emulsion was then poured into a polytetrafluoroethylene mold and completely sealed, and heated and cured at 80°C to form a phase change material. The material had few pores and could not meet the application requirements. The apparent density of the phase change material was measured and the result was 0.519 g / cm 3 ; The thermal conductivity was measured and the result was 0.163W / m·K.

[0183] The temperature and heat flow relationship diagram of the energy storage phase change thermal insulation foam material prepared in Examples 1-6 is as follows: Figure 1 As shown by Figure 1 It can be seen that with the increase of palm wax content, the heat storage capacity of the foam material increases significantly.

[0184] The appearance of the energy storage phase change thermal insulation foam material prepared in Example 1-6 is shown in the figure below: Figure 2 As shown, in the figure, a corresponds to the energy storage phase change thermal insulation foam material prepared in Example 6, and bf correspond to the energy storage phase change thermal insulation foam materials prepared in Examples 1-5 respectively.

[0185] The relationship between the compression strain and stress of the energy storage phase change thermal insulation foam material prepared in Examples 1-6 is shown in the figure Figure 3 As shown by Figure 3 It can be seen that as the palm wax content increases, the compressive stress of the foam material gradually increases. Since palm wax usually exhibits a certain rigidity and toughness in the solid state, by introducing palm wax into the system, the compressive stress of the foam material is increased by 2.7 times compared with the blank control example without phase change material (Example 6).

[0186] The external morphology of the energy storage phase change thermal insulation foam materials prepared in Example 13 and Example 14 is shown in the figure below: Figure 4 shown. Figure 4In the figure: a is the energy storage phase change thermal insulation foam material prepared by a borosilicate cylindrical mold in Example 13, and b is the energy storage phase change thermal insulation foam material prepared by a borosilicate square mold. Since the emulsion has high moldability and has undergone a filling foaming method, various complex geometric shapes can be manufactured by using different types of molds, so that it can adapt to different application requirements and has high flexibility and pertinence.

[0187] The appearance of the energy storage phase change thermal insulation foam materials prepared in Example 3 and Example 13 is as follows: Figure 5 As shown, Figure 5 Where a corresponds to Example 3, and b corresponds to Example 13. Figure 5 It can be seen that: when using polytetrafluoroethylene mold, the foam has no oil film (a in the figure); when using high borosilicate mold, the foam has an oil film (b in the figure). The formation of the oil film can help reduce surface roughness and improve the surface smoothness of the foam material; secondly, the hydrophobicity of the oil film itself can make the foam more water-resistant, thereby improving the durability of the material.

[0188] The scanning electron microscope images of the foam materials prepared in Example 3 and Comparative Example 3 are as follows: Figure 6 shown. Figure 6 Figure a is a scanning electron microscope image of the foam material prepared in Example 3, and figure b is a scanning electron microscope image of the foam material prepared in Comparative Example 3. Figure 6 It can be seen that the unfoamed foam has a low porosity, a dense structure, and uneven pore shape and distribution; in contrast, the foamed foam material has a high porosity and dense pores, among which the larger spherical pores are caused by the growth of the bubble nucleus, and the small pores on the surface of the spherical pores are obtained by evaporation of the emulsion water phase droplets. Such a structure significantly reduces the density and thermal conductivity of the foam material.

[0189] The appearance of the foam materials prepared in Example 3, Comparative Example 1 and Comparative Example 2 is shown in the figure below: Figure 7 As shown, Figure 7 Where a corresponds to Example 3, b corresponds to Example 2, and c corresponds to Example 1. Figure 7 It can be seen that: Figure a is formed by the normally prepared and foamed emulsion, with a relatively large volume, evenly distributed and large number of pores, and a low density; Figure b: Since the bubble nucleus fails to grow normally, the number of pores in the foam is significantly reduced, and the overall structure is relatively tight; Figure c is due to the aggregation and merger of the water phase droplets of the emulsion, resulting in a significantly increased size of the foam pores, a significantly reduced number, and a destroyed structure.

[0190] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing an energy storage phase change thermal insulation foam material, characterized in that: include: Step a), melting, heating and mixing the phase change material and the oil phase to obtain a first mixed oil phase; The phase change material is an ester wax substance or a fusible ester substance; the oil phase is a biomass prepolymer; Step b), adding nanoparticles and an initiator to the first mixed oil phase to obtain a second mixed oil phase; Step c), adding the water phase to the second mixed oil phase, and mechanically stirring and emulsifying to obtain a water-in-oil Pickering emulsion; Step d), adding a foaming agent to the water-in-oil Pickering emulsion to obtain a pre-foamed emulsion; Step e), pouring the pre-foamed emulsion into a mold, heating and curing, and drying after curing to obtain an energy storage phase change thermal insulation foam material.

2. The preparation method according to claim 1, characterized in that: The ester wax substance is one or more of beeswax, insect wax, palm wax, and rice bran wax; the fusible ester substance is one or more of stearic acid ester, hydrogenated castor oil, and fatty acid ester.

3. The preparation method according to claim 2, characterized in that: The mixing ratio of the phase change material to the oil phase is 1-15:100 by weight.

4. The preparation method according to claim 1, characterized in that: The nanoparticles are organic nanoparticles and / or inorganic nanoparticles; the organic nanoparticles are ethyl cellulose nanoparticles, chitin nanoparticles, or phase change nanoparticles, and the phase change nanoparticles are nanoparticles made of phase change materials with a melting temperature higher than 80°C; the inorganic nanoparticles are silicon dioxide particles, calcium carbonate particles or zinc oxide particles; the amount of the organic nanoparticles added to the first mixed oil phase is 2-12wt%; the amount of the inorganic nanoparticles added to the first mixed oil phase is 0.3-1.8wt%.

5. The preparation method according to claim 1, characterized in that: The initiator is benzoyl peroxide, lauroyl peroxide or tert-butyl perbenzoate; the added amount of the initiator is 2-3wt% of the first mixed oil phase.

6. The preparation method according to claim 1, characterized in that: The foaming agent is bicarbonate, and the added amount of the foaming agent is 0.1-1.5wt% of the water-in-oil Pickering emulsion.

7. The preparation method according to claim 1, characterized in that: In the step c), the mixing ratio of the second mixed oil phase to the water phase is 6-9:1-4.

8. The preparation method according to claim 1, characterized in that: In the step e), the temperature of heating and curing is 70-100° C., and the time is 1.5-6 hours; the temperature of drying is 50-60° C., and the time is 6-8 hours.

9. The preparation method according to claim 1, characterized in that: In the step e), the mold material is polytetrafluoroethylene, high borosilicate or stainless steel.

10. An energy storage phase change thermal insulation foam material, characterized in that: It is prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for preparing phase change energy storage materials using microemulsion method and the preparation method thereof

    CN109776718B

  • Composite shape-stabilized phase change energy storage material and preparation method thereof

    CN118421268A

  • Preparation method of organic phase change energy storage composite material

    CN101982475A

  • Composition of plant-based wax

    CN118922501A

  • Expandable polystyrene, polystyrenic foam with excellent function of thermal energy storage prepared from the same, and method for preparing the same

    KR1020120078641A